An Interval Multi-objective Particle Swarm Optimization Algorithm with Niching Technology for Multimodal Problems - Guan, Shouping; Li, Xinyu (Chinese Control and Decision Conference, 2023)
This paper proposes an interval multi-objective niching particle swarm optimization (IMNPSO) algorithm for solving interval multimodal multi-objective optimization problems (IMMOPs). Firstly, in order to locate and maintain multiple optimal solutions, an interval niching PSO (INPSO) algorithm using a ring topology is introduced, and a dual archive mechanism is used to store personal and neighborhood best positions of all particles. Then, a fast non-dominated sorting algorithm based on interval analysis and the interval special crowding distance (ISCD) calculation method are presented, which are combined to form the sorting mechanism of interval particles in IMNPSO. Finally, several multi-objective test functions are selected, and the results demonstrate the effectiveness of the proposed algorithm.